2013
DOI: 10.1111/1471-0528.12224
|View full text |Cite|
|
Sign up to set email alerts
|

The risk of congenital malformations, perinatal mortality and neonatal hospitalisation among pregnant women with asthma: a systematic review and meta‐analysis

Abstract: Background There is conflicting literature on the effect of maternal asthma on congenital malformations and neonatal outcomes.Objectives This review and meta-analysis sought to determine if maternal asthma is associated with an increased risk of adverse neonatal outcomes.Search strategy We searched electronic databases for: (asthma or wheeze) and (pregnan* or perinat* or obstet*). Authors' conclusions Despite limitations related to the observational nature of the primary studies, this review demonstrates a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 61 publications
3
114
1
3
Order By: Relevance
“…Using a 10 cm visual analog scale, where 0 cm represented no perceived risk and 10 cm represented major risk (e.g., birth defects), Powell et al found that women assigned minimal risk to the SABA salbutamol (mean 0.5 cm), with greater perceived risks being associated with ICS use (mean 1.2 cm) and oral corticosteroids (4.5 cm) [40]. A recent systematic review and meta-analysis of over 56,000 pregnancies with asthma and over 1 million pregnancies without asthma from 14 studies found a significant but very small increased risk of congenital malformations among women with asthma compared with women without asthma (RR: 1.11; 95% CI: 1.02-1.21) [41]. In addition, data combined from two studies found an increased risk of cleft lip with or without cleft palate (RR: 1.30; 95% CI: 1.01-1.68).…”
Section: Management Of Asthma During Pregnancy According To the 2008 mentioning
confidence: 99%
“…Using a 10 cm visual analog scale, where 0 cm represented no perceived risk and 10 cm represented major risk (e.g., birth defects), Powell et al found that women assigned minimal risk to the SABA salbutamol (mean 0.5 cm), with greater perceived risks being associated with ICS use (mean 1.2 cm) and oral corticosteroids (4.5 cm) [40]. A recent systematic review and meta-analysis of over 56,000 pregnancies with asthma and over 1 million pregnancies without asthma from 14 studies found a significant but very small increased risk of congenital malformations among women with asthma compared with women without asthma (RR: 1.11; 95% CI: 1.02-1.21) [41]. In addition, data combined from two studies found an increased risk of cleft lip with or without cleft palate (RR: 1.30; 95% CI: 1.01-1.68).…”
Section: Management Of Asthma During Pregnancy According To the 2008 mentioning
confidence: 99%
“…Over the past few years, a large systematic review and a series of meta-analyses have been published that summarise the literature on adverse perinatal outcomes among females with asthma [1][2][3][4]. The first review to be published, in 2011, demonstrated an increased risk of pre-eclampsia, preterm birth, low birth weight and small for gestational age among females with asthma, compared to females without asthma [1].…”
Section: Adverse Perinatal Outcomes Associated With Asthma During Prementioning
confidence: 99%
“…The systematic review and meta-analyses published in 2013 demonstrated a small but significantly increased risk of any congenital malformations among females with asthma (RR 1.11, 95% CI 1.02-1.21), but not of major malformations [2]. Specifically, cleft lip with or without cleft palate was significantly increased among females with asthma compared to females without asthma (RR 1.30, 95% CI 1.01-1.68).…”
Section: Adverse Perinatal Outcomes Associated With Asthma During Prementioning
confidence: 99%
“…A summary of the early literature was published in 2007 [1]. Since then further studies have appeared and recent reviews are available [2,3]. A meta-analysis in the latter article found a weighted total odds ratio for a major malformation from four relatively large cohort studies of 1.18 (95% CI 1.00-1.36).…”
Section: Introductionmentioning
confidence: 99%